Imported Schistosomiasis: A New Public Health Challenge for China - Wang, Lei; Wu, Xiaoying; Li, Xiaoli; Zheng, Xiaoyan; Wang, Fei; Qi, Zhiqun; Huang, Minjun; Zou, Yang (Frontiers in Medicine, 2020)
The imported schistosomiasis cases have been significantly increased in China as economy grows. The aim of this study is to review and characterize the current status, clinical features and transmission risk of imported infections of Schistosoma mansoni and S. haematobium in China. A retrospective study was performed to review all information regarding the imported cases of schistosomiasis collected from published literature and database of National Notifiable Disease Report System (NNDRS) from 1979 to 2019. The characterization of epidemiological and clinical features was analyzed. Total 355 cases of imported schistosomiasis have been reported in 15 provinces (autonomous regions, municipalities) in China since 1979, including 78 cases infected with S. mansoni (21.97%), 262 cases with S. haematobium (73.80%) and 15 cases with un-identified Schistosoma species. Eosinophilia was the most common sign of infection of S. mansoni (91.03%). The parasitological findings were confirmed in 89.74% (70/78) of cases infected with S. mansoni and 32.06% (84/262) of cases infected with S. haematobium. There was no imported case of S. japonicum, S. intercalatum or S. mekongi reported in China during this period. Given that snail Biomphalaria straminea, the intermediate host of S. mansoni has already been found in south China, the imported cases of S. mansoni infection increase the risk of its transmission and spread in the regions. Thus, the better understanding of the clinical features and transmission pattern of these Schistosoma infections will assist Chinese physicians to diagnose and treat patients with schistosomiasis imported from foreign countries.